ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN PEMBAYARAN ZAKAT DARING - Karim, Nina Karina; Atikah, Siti; Lenap, Indria Puspitasari (Jurnal Riset Akuntansi, 2024)
Payment of daily transactions nowadays can be done online, including zakat. This research aims to analyze the factors that influence the intention of different generation classification in using online zakat payment systems based on the criteria set in the Technology Acceptance Model (TAM). Questionnaires in the form of Google Form were distributed through social media channels and was answered by 121 respondents. The data collected from the questionnaires revealed that online payment systems for zakat is still not preferred by Baby boomers, Gen X, Gen Y and Gen Z because it is considered unable to ensure that the zakat given is appropriate for both the mustahik and muzaki. Respondents are also not sure that paying zakat online will ensure that the zakat will be passed on to eligible mustahik.